Consumption of benzylpenicillin as a syphilis control indicator (Brazilian Journal of Pharmaceutical Sciences, 2023)
Syphilis is a disease with compulsory and mandatory notification to the Notifiable Diseases Information System (SINAN), with benzathine benzylpenicillin being the treatment of choice. The aim of the study was to compare the consumption of benzylpenicillin benzathine, from the dispensation, between the health regions of a capital in the southern region of the country, according to the georeferencing of notified cases of syphilis. This is a descriptive, cross-sectional, retrospective study of the use of benzylpenicillin benzathine and of reported cases of syphilis. Data on syphilis cases were obtained from notifications made in SINAN, and drug consumption data were obtained from the Municipal Health Department computerized system for Drug Dispensing from January 1st, 2019 to December 31st, 2019. Notifications and drug consumption were georeferenced according to 8 health regions. From the compilation of data, the rates of cases and consumption in relation to the population of each region were calculated. A total of 3188 notifications and a total of 35191 vials of benzathine benzylpenicillin were analyzed. The ratio of vials by SINAN notifications showed that each patient took 11 vials of the drug, which is a higher value if we consider that the complete treatment is 2 to 6 vials per case.